pengaruh pendekatan levelling sistem terhadap peningkatan kemampuan passing bawah bola voly - Rohayati, Yati; Lengkana, Anggi Setia; Supriyadi, Tedi (Jurnal Porkes, 2024)
Based on the author's observations, students at SDN Ambit tend to be less enthusiastic, lazy, and passive when participating in volleyball learning activities. The purpose of this study was to determine whether lower passing training using the leveling system approach has an effect on improving lower passing skills in volleyball learning in Ambit Elementary School students. This researcher used a quantitative approach. This research design uses a pre-experimental design type experiment, namely the one group pretest posttest design. The population in this study were Ambit Elementary School students totaling 24 children. The sample technique for this study used purposive sampling technique, with the criteria of upper grades who still cannot do lower passing during volleyball learning. analyze data using normality test, homogeneity test, paired sample T-test, and r-square regression test. The research results of the pretest and posttest results on the ability to pass down in volleyball learning obtained an average pretest score of 9.08, with the lowest score of 3 and the highest score of 26. While the average posttest was 17.83, with the lowest score of 3 and the highest score of 45. Based on the data normality test conducted using Kolmogorov-Smirnov, the pretest value was 0.026, while the posttest was 0.06. It can be concluded that the data is normally distributed because the significance value obtained is > 0.05, so H0 is accepted. the conclusion is that this study shows that using lower passing training with a leveling system approach has an effect on improving lower passing ability in volleyball learning in Ambit Elementary School students.